Hak Kekayaan Intelektual Pada Situs Internet : Suatu Tinjauan dan Analisis Normatif - Agung Gumelar (Jurnal Hukum dan Sosial Politik, 2023)
This article has the aims and objectives to be obtained, namely to find out and analyze the importance of the existence of Intellectual Property Rights (IPR) on internet sites, and how forms of regulation based on positive law in Indonesia. This study uses a normative legal research method with a statutory approach, the data sources used are primary data and secondary data. The results of the research have shown that the existence of IPR on internet sites has basic values ​​and objectives, namely as legal protection for creators owned by individuals or groups. for his hard work in making copyrighted works with economic value contained therein and Anticipating and also preventing violations of IPR belonging to other people, HKI is also currently regulated in various legal constructions that apply in Indonesia, such as Law Number 28 Year 2014 concerning Copyright, Law no. 15 of 2001 concerning Marks and other implementing regulations. With the objectives and construction of the applicable law, it is actually important for the government to continue to optimize and review the application of the law periodically in order to prevent IPR violations on internet sites carried out by cybercrimes.